2017
DOI: 10.5603/arm.2017.0016
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Status and Its Relationship to Chronic Respiratory Disease

Abstract: Socioeconomic status (SES) is defined as an individual's social or economic standing, and is a measure of an individual's or family's social or economic position or rank in a social group. It is a composite of several measures including income, education, occupation, location of residence or housing. Studies have found a lower SES has been linked to disproportionate access to health care in many diseases. There is emerging data in pulmonary diseases such as COPD, asthma, cystic fibrosis, pulmonary hypertension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
67
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 61 publications
8
67
0
2
Order By: Relevance
“…This is similar to the results from a Danish study, which found that university graduates and people with ⩾10 years of education presented lower rates of disease compared to those with <10 years of education [51]. In particular, a significant interplay seems to exist between COPD and socioeconomic status [52][53][54][55][56][57]. A significant negative correlation between lung function ( primarily forced expiratory volume in 1 s and forced vital capacity) and socioeconomic status has been established [54].…”
Section: Socioeconomic Status and Copdsupporting
confidence: 77%
See 1 more Smart Citation
“…This is similar to the results from a Danish study, which found that university graduates and people with ⩾10 years of education presented lower rates of disease compared to those with <10 years of education [51]. In particular, a significant interplay seems to exist between COPD and socioeconomic status [52][53][54][55][56][57]. A significant negative correlation between lung function ( primarily forced expiratory volume in 1 s and forced vital capacity) and socioeconomic status has been established [54].…”
Section: Socioeconomic Status and Copdsupporting
confidence: 77%
“…A relationship exists even after adjusting for smoking status, occupational exposure and race [54]. Smoking is associated with a greater absolute mortality risk due to lung cancer or COPD for individuals in lower socioeconomic groups [55][56][57][58]. Income is inversely associated with COPD treatment initiation [57].…”
Section: Socioeconomic Status and Copdmentioning
confidence: 99%
“…Asthma appears to be a major underlying risk factor for COPD evidenced by the finding that up to 30% of COPD patients are asthmatics (Soriano et al, 2003) and that a more rapid decline in lung function is observed in smokers with asthma than those without (Lange, Parner, Vestbo, Schnohr, & Jensen, 1998). Finally, population groups with poorer social-economic status tend to have a greater risk of developing COPD and its complications than their wealthier counterparts (Fragoso, 2016;Lawlor, Ebrahim, & Davey Smith, 2004;Sahni, Talwar, Khanijo, & Talwar, 2017;Shohaimi et al, 2004), which is likely to be related to poor nutritional status, living standard, exposure to pollutants and high smoking rate along with poor access to health care.…”
Section: Causes and Pathophysiology Of Copdmentioning
confidence: 99%
“…It was estimated that the burden of chronic diseases, including CRDs, accounted for 80% of the total burden in developing countries [7]. A negative association of socioeconomic status with the prevalence in COPD was revealed [8]. Asthma prevalence was found to be highest in high-income regions [9].…”
Section: Introductionmentioning
confidence: 97%